Successful termination of mummified foetus in a primiparous Deoni heifer - MARKANDEYA, N M; DESHPANDE, A V; BHARKAD, G P; BHIKANE, A U (The Indian Journal of Animal Reproduction, 2023)
A case of mummilication of fodus recorded in Denni primiparous cow has been reported with its successful terminationby using valathamide bromide and prostaglandins.